Some optical and transport properties of a new subclass of ceramic tungstates and molybdates. Issue 10 (December 2015) - Sawicki, B.; Groń, T.; Tomaszewicz, E.; Duda, H.; Górny, K.
Abstract: UV–vis–NIR and electrical investigation of AgY1− x (Gd, Nd) x (WO4 )2 and MRE2 W2 O10 (M=Cd, Co, Mn; RE=Y, Nd, Sm–Er) tungstates as well as Cd1−3 x Gd2 x □ x MoO4 molybdates proved them to be in the insulating state. The calculated value of the direct allowed energy gap E g >2.4 eV. Only for CoPr2 W2 O10, MnPr2 W2 O10 and Cd1−3 x Gd2 x □ x MoO4 solid solutions when 0.0238≤ x ≤0.0839, thermally activated conduction of the Arrhenius-type was observed. The I–V measurements at higher temperatures showed lower carrier emission for AgY1− x (Gd, Nd) x (WO4 )2 solid solutions and higher ones for the remaining samples. Colossal increase in electron emission of MPr2 W2 O10 (M=Co, Mn) and in Cd1−3 x Gd2 x □ x MoO4 for 0.0098 ≤ x ≤0.0839 at 400 K is interpreted in the framework of the Poole–Frenkel effect and a small polaron mechanism, respectively.